Intracellular cyclic AMP inhibits native and recombinant volume-regulated chloride channels from mammalian heart - Nagasaki, Masaaki (Blackwell Science Inc, 2000)
1. ClC-3 encodes a volume-regulated Cl(−) channel (I(Cl,vol)) in heart. We studied the regulation of native and recombinant cardiac I(Cl,vol) by intracellular cyclic AMP (cAMP(i)). 2. Symmetrical high Cl(−) concentrations were used to effectively separate outwardly rectifying I(Cl,vol) from other non-rectifying Cl(−) currents, such as the cystic fibrosis transmembrane conductance regulator (CFTR) and Ca(2+)-activated Cl(−) currents (I(Cl,CFTR) and I(Cl,Ca), respectively), which are concomitantly expressed in cardiac myocytes. 3. 8-Bromo-cyclic AMP (8-Br-cAMP) significantly inhibited I(Cl,vol) in most guinea-pig atrial myocytes. In ≈30 % of the atrial myocytes examined, 8-Br-cAMP increased macroscopic Cl(−) currents. However, the 8-Br-cAMP-stimulated difference currents exhibited a linear current-voltage (I–V) relation, consistent with activation of I(Cl,CFTR), not I(Cl,vol). 4. In canine atrial myocytes, isoprenaline (1 μM) consistently reduced I(Cl,vol) in Ca(2+)-free hypotonic bath solutions with strong intracellular Ca(2+) ([Formula: see text]) buffering. In Ca(2+)-containing hypotonic bath solutions with weak [Formula: see text] buffering, however, isoprenaline increased net macroscopic Cl(−) currents. Isoprenaline-stimulated difference currents were not outwardly rectifying, consistent with activation of I(Cl,Ca), not I(Cl,vol). 5. In NIH/3T3 cells transfected with gpClC-3 (the gene encoding I(Cl,vol)), 8-Br-cAMP consistently inhibited I(Cl,ClC-3). These effects were prevented by a protein kinase A (PKA) inhibitor, KT5720, or by mutation of a single consensus protein kinase C (PKC) phosphorylation site (S51A) on the N-terminus of ClC-3, which also mediates PKC inhibition of I(Cl,ClC-3). 6. We conclude that cAMP(i) causes inhibition of I(Cl,vol) in mammalian heart due to cross-phosphorylation of the same PKC consensus site on ClC-3 by PKA. Our results suggest that contamination of macroscopic I(Cl,vol) by I(Cl,CFTR) and/or I(Cl,Ca) may account for some of the inconsistent and controversial effects of cAMP(i) on I(Cl,vol) previously reported in native cardiac myocytes.